The Relationship of Exposure to PM 10 and PM 2.5 Dust with Respiratory Disorders in Lime Stone Mining Workers: Literature Review - Prasetyo Adi Nugroho; Onny Setiani; Yusniar Hanani D (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction:Karst areas are natural formations formed from carbonate rocks such as limestone and chalk over thousands of years, storing biological and non-biological resources. Although limestone quarries provide an economic source of income, their impact on the environment and health is often negative, especially through air pollution by particulates such as PM10 and PM2.5. Lime dust can cause lung problems, eye irritation and respiratory system problems, especially for lime mine workers. The limestone industry generally operates informally, often ignoring health and safety protections. Objective: To analyze the relationship between exposure to PM 10 and PM 2.5 dust with respiratory disorders in limestone mining workers. Method: Literature review from various studies and journals relevant to the research objectives over the last 10 years. Results: There is a relationship between length of work, age, smoking, and history of illness with respiratory disorders in limestone mine workers. Conclusion: There is a relationship between exposure to PM 10 and PM 2.5 dust and respiratory disorders in limestone mining workers.